Phonological Mean Length of Utterance (PMLU) in typically developingtelugu speaking children: A developmental perspective - Kalyani B; Lakshmi Prasanna Swamini; Vani Rupela; Lakshmi Venkatesh (Journal of All India Institute of Speech and Hearing, 2013)
Phonological MLU or pMLU is a measure of whole word complexity that gives an indicator of phonological development. The objective of the current study was to study phonological skills of Telugu speaking typically developing children using pMLU as a measure. Cross-sectional data were collected from fifty typically developing Telugu-speaking children. Children were divided into five age groups from 2;6 to 5;0 years of age. As age increased, the pMLU also increased and the five age groups were significantly different from each other. Overall, the pMLUs were larger than those of English- and Hindi- speaking children and similar to those of Kannada-speaking children. Further, pMLUs of five mental age matched children with Down syndrome are presented in comparison to those obtained from typically developing children. Children with Down syndrome demonstrated pMLUs which were significantly lower than those of the typically developing children. Results are discussed from a crosslinguistic perspective highlighting the limitations and usefulness of pMLU in the Indian context.